A darkness forged in fire - Evans, Chris (Chris R.) (New York : Pocket Books, 2008)
Konowa Swift Dragon, former commander of the Empire's elite Iron Elves, is looked upon as anything but ordinary. He's murdered a Viceroy, been court-martialed, seen his beloved regiment disbanded, and finally been banished in disgrace to the one place he despises the most -- the forest. Now, all he wants is to be left alone with his misery...but for Konowa, nothing is ever that simple. The mysterious and alluring Visyna Tekoy, the highborn daughter of an elfkynan governor, seeks him out in the dangerous wild with a royal decree that he resume his commission as an officer in Her Majesty's Imperial Army, effective immediately. His assignment: reach the Red Star (a star heralding the return of a magic long vanished from the Earth) before the dreaded Shadow Monarch, a legendary elf-witch.--From publisher description.
Keywords: Soldiers -- fiction; Magic -- Fiction